Design of a test execution of strategies for learning of university students - González Lomelí, Daniel (Consorcio de Universidades Mexicanas A.C., 2014)
The objective of this study was to design and validate a test on learning strategies, in an execution context from a multidimensional model of evaluation. Through an Analysis of Cognitive Task (ACT) identified the types of content to be evaluated and the cognitive operations that underlie learning the content of the text Strategies to learn how to learn on the subject of the same name, a public university in the northwest of Mexico. From the results of the ACT was developed a test of Learning Strategies (EPA) formed with 28 reagents, which are applied to an intentional sample of 144 undergraduate students. A Rasch analysis resulted in a test of 26 reagents, subsequently were confirmatory factorial analysis, through structural equation modeling, by types of knowledge (declarative and procedural) and by execution context (recognition and remembrance); two models were obtained with appropriate adjustment to the data according to the indices more accepted. Engineering students gain a greater performance in the EPA test to be evaluated in the context of remembrance, in comparison with those of psychology.